Two Kinds of Proteases Improved the Water-holding Capacity and Quality of Phosphorus-reduced Steak - Xiaojuan JIANG; Deyin PAN; Bing LI; Hongsheng CHEN; Jingjing DIAO (Shipin gongye ke-ji)
In this study, the effects of papain and glutamine transaminase on the water-holding capacity and quality of phosphorus-reduced steaks were investigated. Fresh bovine outer spine meat was studied in a one-way test using water-holding capacity, low-field nuclear magnetic resonance relaxation time, scanning electron microscopy, and shear force as evaluation indices. Effects on the water-holding capacity, processing quality, and organoleptic quality of steaks were compared for the control group (non-additive), phosphate group (phosphate additions of 0.2% and 0.4%), papain phosphorus-reduced group (0.2% phosphate with concentrations of 0.03%, 0.05% and 0.07% papain), and glutamine aminotransferase phosphorus-reduced group (0.2% phosphate with concentrations of 0.4%, 0.6%, and 0.8% glutamine aminotransferase). The results showed that the addition of 0.05% papain significantly reduced (P<0.05) steak cooking loss by 4.89% and shear force by 25.67 N and improved steak organoleptic quality when compared to the effects for the 0.2% phosphate group, and there were no significant difference (P>0.05) compared with the 0.4% phosphate group. Therefore, use of this treatment could effectively replace 50% of the amount of phosphate in the steak. In the glutamine aminotransferase phosphorus-reduced group, both cooking loss and shear force gradually decreased with an increase in the addition of glutamine aminotransferase, and no significant improvement (P>0.05) in product quality was noted when the added amount was greater than 0.6%. In conclusion, papain treatment at a concentration of 0.05% could effectively replace the addition of certain phosphates during meat processing and provide new ideas for the production of green, clean, and phosphorus-reduced meat products.